2006
DOI: 10.1016/j.jacc.2005.08.066
|View full text |Cite
|
Sign up to set email alerts
|

T-Wave Alternans and the Susceptibility to Ventricular Arrhythmias

Abstract: T-wave alternans (TWA) reflects beat-to-beat fluctuations in the electrocardiographic T-wave, and is associated with dispersion of repolarization and the mechanisms for sudden cardiac arrest (SCA). This review examines the bench-to-bedside literature that, over decades, has linked alternans of repolarization in cellular, whole-heart, and human studies with spatial dispersion of repolarization, alternans of cellular action potential, and fluctuations in ionic currents that may lead to ventricular arrhythmias. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
288
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(300 citation statements)
references
References 95 publications
(117 reference statements)
6
288
0
6
Order By: Relevance
“…19,23 TWA has been shown to reflect the presence of abnormal repolarization and electrophysiologic inhomogeneities that underlie vulnerability to ventricular fibrillation. 19 Measurement of TWA during controlled heart rate elevation is considered as a potentially useful predictor of ventricular arrhythmic events and mortality in patients with ischemic cardiomyopathy, 3 and its role in identification of patients that would benefit ICD implantation is being currently studied. 6 TWA amplitudes are in the range of microvolts, and can be even below the noise level, making the detection of TWA a difficult task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,23 TWA has been shown to reflect the presence of abnormal repolarization and electrophysiologic inhomogeneities that underlie vulnerability to ventricular fibrillation. 19 Measurement of TWA during controlled heart rate elevation is considered as a potentially useful predictor of ventricular arrhythmic events and mortality in patients with ischemic cardiomyopathy, 3 and its role in identification of patients that would benefit ICD implantation is being currently studied. 6 TWA amplitudes are in the range of microvolts, and can be even below the noise level, making the detection of TWA a difficult task.…”
Section: Introductionmentioning
confidence: 99%
“…12 Two commercially available techniques are the spectral method (SM) 23,26 and the modified moving average method 22 ; alternative techniques are the complex demodulation method 20 and the Laplacian likelihood ratio method (LLR). 11,13 A major limitation of these methods is their poor sensitivity to low-amplitude alternans 12,19 due to a lack of robustness to noise. With SM, for example, a noise level ‡ 2 lV in a predefined spectral band can lead to an indeterminate TWA test.…”
Section: Introductionmentioning
confidence: 99%
“…The TWA in CHF and Ohio/Michigan studies (14,21) reported higher event rates in patients with QRS widening, but neither reported NPV of TWA based on QRS width. This issue is important for the bedside application of TWA to individual patients, and may be clarified by the formal subgroup analysis of the ABCD and SCD-HefT TWA substudy or other ongoing trials of TWA (13).…”
mentioning
confidence: 99%
“…Since patients with wide QRS were more likely to receive ICDs, this may have led to 'over-reporting' of nonfatal arrhythmias compared to patients with narrow QRS. In addition, Morin et al (17) continued beta-blockers during TWA testing, that may theoretically attenuate TWA and impair its NPV (13). On the other hand, recent TWA trials reported high NPV for TWA either with (21) or without (14) continued betablockade during testing.…”
mentioning
confidence: 99%
“…Moreover, we examined heart rate variability as an established predictor of increased mortality and elevated risk of cardiac events in the general population 14. T‐wave alternans that displays heterogeneity in ventricular repolarization and thus predicts ventricular arrhythmias in patients at risk for sudden cardiac death was additionally registered 15. Both 12‐lead ECG and Holter recording were analysed by experienced cardiologists, blinded to the patients' clinical background information.…”
Section: Methodsmentioning
confidence: 99%